Design of the application programming interface for a Pilot RESTful grid service - Demichev, A.P.; Ilyin, V.A.; Kryukov, A.P.; Shamardin, L.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
The design principles of the application programming interface for the RESTful grid services are described. The basic elements of the application programming interface for the Pilot multistage workflow jobs execution service are discussed. Some general approaches to the interface design of such services are analyzed. Several methods for the indempotent invocation of complex operations are proposed. Different approaches to the authentication of RESTful grid services are considered.